2016
DOI: 10.1007/s11695-016-2454-z
|View full text |Cite
|
Sign up to set email alerts
|

Weight Loss Analysis According to Different Formulas after Sleeve Gastrectomy With or Without Antral Preservation: a Randomised Study

Abstract: Group 3 cm obtained a lower percentage of suboptimal results using EWL. %TWL places the 3 cm group in higher percentile than 8 cm group. Through EBMI, both groups are equally effective. It is necessary to have standardised dynamic tables for each surgical technique, becoming essential elements to measure weight loss after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 19 publications
1
10
0
2
Order By: Relevance
“…The search yielded 197 articles. After de-duplication and exclusions ( Figure 1), a total of eight studies remained which provided data for a total of 619 patients (8,11,(17)(18)(19)(20)(21)(22) . Table 1 summarizes the participants and interventions for the included studies.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The search yielded 197 articles. After de-duplication and exclusions ( Figure 1), a total of eight studies remained which provided data for a total of 619 patients (8,11,(17)(18)(19)(20)(21)(22) . Table 1 summarizes the participants and interventions for the included studies.…”
Section: Study Selectionmentioning
confidence: 99%
“…Seven studies reported on this outcome, five of which were RCTs (8,11,18,20,21) , (Figure 2). Only one RCT found a statistically significant difference in 12 month %EWL and this was in favor of AR (11) .…”
Section: Weight Loss At 12 Months Post-surgery (12 Month %Ewl)mentioning
confidence: 99%
“…Las variables clínicas de interés se extrajeron manualmente de las HCE. Los resultados del procedimiento bariátrico reportaron mediante el porcentaje de pérdida de peso total (%TWL) dado por la fórmula [(peso inicial -peso actual) / (peso inicial)] × 100 [19][20][21] , el porcentaje de pérdida de IMC dado por la fórmula (IMC inicial -IMC final / IMC inicial) × 100 22 , y el porcentaje de pérdida de exceso de peso (%EWL), dado por la fórmula [(peso inicial -peso actual) / (peso inicial -peso ideal)] x 100, utilizando un IMC ideal de 25 kg/m 2 23,24 . Estos parámetros, al igual que la mejoría y remisión de comorbilidades, se evaluaron al año y dos años posquirúrgicos, con un período de ventana de 3 meses para la recolección de datos.…”
Section: Resultados De Interésunclassified
“…Los resultados sugieren que la cirugía bariátrica es un tratamiento eficaz para la obesidad y sus comorbilidades en este grupo etario, con una baja tasa de complicaciones, demostrando resultados similares a los estudios realizados en otros países 33 . Los pacientes adultos mayores que se sometieron a bypass gástrico o gastrecto-mía en manga mostraron una reducción de peso estadísticamente significativa, obteniendo valores de %TWL y %EWL concordantes con aquellos descritos en otros estudios: ≥ 20% para el primero 19 , y ≥ 50% para el segundo, de acuerdo con los criterios de Reinhold 21,23 , tanto a uno como a dos años de seguimiento. Las complicaciones descritas en este análisis son en su mayoría leves, de manera similar a aquellas reportadas en estudios de adultos jóvenes 14,34 , demostrando la seguridad de la cirugía bariátrica en adultos mayores, así como lo han determinado otros artículos publicados 35,36 ; apoyando así la afirmación de que una edad avanzada por sí sola no debe considerarse una contraindicación para el tratamiento quirúrgico de la obesidad.…”
Section: Discussionunclassified
“…Further, the distance from pylorus at which the stomach division should be started is still not standardized and has been reported varying from two to 8cm. 7 - 9 …”
Section: Introductionmentioning
confidence: 99%